Type 1 Diabetes Patients With Different Residual Beta-Cell Function but Similar Age, HBA1c, and Cardiorespiratory Fitness Have Differing Exercise-Induced Angiogenic Cell Mobilisation - Taylor, Guy S.; Shaw, Andy; Scragg, Jadine H.; Smith, Kieran; Campbell, Matthew D.; McDonald, Timothy J.; Shaw, James A.; Ross, Mark D.; West, Daniel J. (Frontiers in Endocrinology, 2022)
Background Many individuals with type 1 diabetes retain residual beta-cell function. Sustained endogenous insulin and C-peptide secretion is associated with reduced diabetes related complications, but underlying mechanisms remain unclear. Lower circulating numbers of endothelial and hematopoietic progenitor cells (EPCs and HPCs), and the inability to increase the count of these cells in response to exercise, are also associated with increased diabetes complications and cardiovascular disease. It is unknown whether residual beta-cell function influences HPCs and EPCs. Thus, this study examined the influence of residual beta-cell function in type 1 diabetes upon exercise-induced changes in haematopoietic (HPCs) and endothelial progenitor cells (EPCs). Methods Participants with undetectable stimulated C-peptide (n=11; Cpepund), 10 high C-peptide (Cpephigh; >200 pmol/L), and 11 non-diabetes controls took part in this observational exercise study, completing 45 minutes of intensive walking at 60% V˙O2peak. Clinically significant HPCs (CD34+) and EPCs (CD34+VEGFR2+) phenotypes for predicting future adverse cardiovascular outcomes, and subsequent cell surface expression of chemokine receptor 4 (CXCR4) and 7 (CXCR7), were enumerated at rest and immediately post-exercise by flow cytometry. Results Exercise increased HPCs and EPCs phenotypes similarly in the Cpephigh and control groups (+34-121% across phenotypes, p<0.04); but Cpepund group did not significantly increase from rest, even after controlling for diabetes duration. Strikingly, the post-exercise Cpepund counts were still lower than Cpephigh at rest. Conclusions Residual beta-cell function is associated with an intact exercise-induced HPCs and EPCs mobilisation. As key characteristics (age, fitness, HbA1c) were similar between groups, the mechanisms underpinning the absent mobilisation within those with negative C-peptide, and the vascular implications, require further investigation.